The late works of Hayao Miyazaki : a critical study, 2004-2013 - Cavallaro, Dani, 1962- (McFarland & Company, Inc., Publishers, 2015)
"Once a favorite of mainly art house audiences, Hayao Miyazaki's films have enjoyed increasing exposure in the West since his Spirited Away won the Oscar for Best Animated Feature in 2003. The award signaled a turning point for Miyazaki's Studio Ghibli, bringing his films prominence in the media and driving their distribution in multiple formats"--